A first-in-human study of 11C-MTP38, a novel PET ligand for phosphodiesterase 7 - Kubota, Manabu; Seki, Chie; Kimura, Yasuyuki; Takahata, Keisuke; Shimada, Hitoshi; Takado, Yuhei; Matsuoka, Kiwamu; Tagai, Kenji; Sano, Yasunori; Yamamoto, Yasuharu; Okada, Maki; Kikuchi, Tatsuya; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2021)
Purpose Phosphodiesterase 7 (PDE7) is an enzyme that selectively hydrolyses cyclic adenosine monophosphate, and its dysfunction is implicated in neuropsychiatric diseases. However, in vivo visualization of PDE7 in human brains has hitherto not been possible. Using the novel PET ligand 11 C-MTP38, which we recently developed, we aimed to image and quantify PDE7 in living human brains. Methods Seven healthy males underwent a 90-min PET scan after injection of 11 C-MTP38. We performed arterial blood sampling and metabolite analysis of plasma in six subjects to obtain a metabolite-corrected input function. Regional total distribution volumes ( V T s) were estimated using compartment models, and Logan plot and Ichise multilinear analysis (MA1). We further quantified the specific radioligand binding using the original multilinear reference tissue model (MRTM O ) and standardized uptake value ratio (SUVR) method with the cerebellar cortex as reference. Results PET images with 11 C-MTP38 showed relatively high retentions in several brain regions, including in the striatum, globus pallidus, and thalamus, as well as fast washout from the cerebellar cortex, in agreement with the known distribution of PDE7. V T values were robustly estimated by two-tissue compartment model analysis (mean V T = 4.2 for the pallidum), Logan plot, and MA1, all in excellent agreement with each other, suggesting the reversibility of 11 C-MTP38 binding. Furthermore, there were good agreements between binding values estimated by indirect method and those estimated by both MRTM O and SUVR, indicating that these methods could be useful for reliable quantification of PDE7. Because MRTM O and SUVR do not require arterial blood sampling, they are the most practical for the clinical use of 11 C-MTP38-PET. Conclusion We have provided the first demonstration of PET visualization of PDE7 in human brains. 11 C-MTP38 is a promising novel PET ligand for the quantitative investigation of central PDE7.